Estimating the biomass of Carex cinerascens (Cyperaceae) in floodplain wetlands in Poyang Lake, China. Issue 1 (1st January 2019) - Li, Ya; Yu, Xiubo; Guo, Qun; Liu, Yu; Xia, Shaoxia; Zhang, Guangshuai; Zhang, Quanjun; Duan, Houlang; Zhao, Liang
Abstract: The estimation of wetland plant biomass is key to understanding the dynamic changes of the structure and functions of wetland ecosystems. Relatively few studies on the spatiotemporal dynamics of wetland plant biomass have been conducted because of the difficulties in obtaining detailed and accurate data. Carex cinerascens meadows are important patches in Poyang Lake in eastern China and provide significant food resources and habitats for wintering waterbirds, particularly geese. We proposed a method to estimate the biomass of C. cinerascens in a subsection of Poyang Lake, i.e. Baisha Lake, employing the digital elevation model and water level gradient of the lake combined with the logistic regression model based on data from field measurements in different elevations. We obtained four C. cinerascens biomass estimation models based on four elevations divided. The maximum biomass decreased with decreasing elevation. Meanwhile, the maximum growth rate initially increased and subsequently decreased. The biomass of C. cinerascens per unit area ranged from 0.10 to 0.58 kg/m 2 in the autumn and winter. Significant differences in the growth process of C. cinerascens were observed in different water level gradients. The total biomass of C. cinerascens in Baisha Lake changed following an S-shaped curve and reached 221, 503, and 615 t in the middle of October, November, and December, respectively. The research results can be used to forecast the biomass of C. cinerascens under different hydrological conditions in Poyang Lake, and to provide wetland plant biomass estimation methods for other similar regions.